2016
DOI: 10.3892/mmr.2016.4771
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of WWP2 suppresses proliferation, and induces G1 cell cycle arrest and apoptosis in liver cancer cells

Abstract: Primary liver cancer is one of the most common and aggressive human malignancies worldwide. As numerous studies have revealed that WW domain containing E3 Ub‑protein ligase 2 (WWP2) exerts cancer‑specific functions, the present study assessed the role of WWP2 in liver cancer. WWP2 was revealed to be significantly overexpressed in liver cancer tissues compared with paired normal tissues at the mRNA as well as at the protein level. Furthermore, small interfering RNA-mediated WWP2 knockdown in liver cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The NEDD4 family members WWP1 and WWP2 are also necessary in regulating apoptosis. Depletion of WWP1 altered Bcl-2-associated X protein (Bax) expression, leading to osteosarcoma cell apoptosis (Wu et al, 2015), while the knockdown of WWP2 promoted G1 cell cycle arrest and apoptosis in liver cancer cells by elevating the expression of apoptosis-associated markers, including caspase-7, caspase-8 and Bax (Xu et al, 2016) (Table S2).…”
Section: Regulation Of Apoptosismentioning
confidence: 99%
“…The NEDD4 family members WWP1 and WWP2 are also necessary in regulating apoptosis. Depletion of WWP1 altered Bcl-2-associated X protein (Bax) expression, leading to osteosarcoma cell apoptosis (Wu et al, 2015), while the knockdown of WWP2 promoted G1 cell cycle arrest and apoptosis in liver cancer cells by elevating the expression of apoptosis-associated markers, including caspase-7, caspase-8 and Bax (Xu et al, 2016) (Table S2).…”
Section: Regulation Of Apoptosismentioning
confidence: 99%
“…Overexpression of miR‐188 suppressed glioma cell proliferation and cell cycle G1–S transition, whereas inhibition of miR‐188 promoted glioma cell proliferation (N. Li et al, ). Furthermore, small interfering RNA‐mediated WWP2 knockdown in liver cancer cell lines was demonstrated to inhibit cell proliferation, cause cell cycle arrest in G1 phase and induction of apoptosis as revealed by a CCK‐8 assay and flow cytometric analysis (Xu et al, ). Our results demonstrated that miR‐188 inhibited breast cancer cell growth and proliferation, which might be ascribed to G1 cell cycle arrest, indicating that cell cycle progression is blocked.…”
Section: Discussionmentioning
confidence: 99%
“…The RUNX3 protein can regulate cell growth and apoptosis, as well as signal transduction and biological processes, through a variety of complex mechanisms. 11,12 The expression of RUNX3 was found to be downregulated or even absent in malignant tumors such as gastric cancer. 13,14 This reduced expression of RUNX3 was accompanied by enhanced proliferation and reduced cell apoptosis in gastrointestinal epithelial cells, leading to their abnormal growth and differentiation, and consequently tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%